Miteinander leben: Ethische Perspektiven eines komplexen Verhältnisses. Vadian Lectures Band 2 - Meier Kressig, Marcel; Lindenau, Mathias (transcript, 2016)
Even if humans are beings capable of self-determination, they cannot live in a fully self-sufficient fashion. As a social being, they rely on their fellow humans, and must confront the complex questions of how we are to live together. It becomes explosive when different forms and conceptions of life clash, which are not readily able to be reconciled. In this second volume of the Vadian Lectures, Heinz Kleger, Alois Riklin, Martin Hartmann and Ludwig Hasler shed light on the various facets of human coexistence.